2022
DOI: 10.1021/acs.jced.2c00236
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Vapor Pressure Data from Gas–Liquid Chromatography Retention Times: Analysis of Multiple Reference Approaches, Review of Prior Applications, and Outlook

Abstract: Reliable methods for determining the vapor pressures of organic materials are of increasing importance as a tool for predicting the behavior and fate of chemicals that are introduced into the environment. In the present work, we analyze the method that relates the gas–liquid chromatography (GLC) retention data, namely, the retention factors (k) of selected organic compounds with their vapor pressures (p 0) using multiple reference standards. Temperature-dependent k values of test chemicals and an adequate numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 204 publications
0
3
0
Order By: Relevance
“…This method was extensively used primarily for the determination of vapor pressures, as it is relatively fast and insensitive to impurities. Our previously published analysis of published CGC results [ 55 ] revealed that many approximations and extensive extrapolations used in the CGC method can lead to large systematic errors. The second reason for rejection is that DMF was used by Panneerselvam et al [ 54 ] as a reference compound with a known vaporization enthalpy taken from the paper by Barone et al [ 16 ], and it is therefore not an independent value.…”
Section: Resultsmentioning
confidence: 99%
“…This method was extensively used primarily for the determination of vapor pressures, as it is relatively fast and insensitive to impurities. Our previously published analysis of published CGC results [ 55 ] revealed that many approximations and extensive extrapolations used in the CGC method can lead to large systematic errors. The second reason for rejection is that DMF was used by Panneerselvam et al [ 54 ] as a reference compound with a known vaporization enthalpy taken from the paper by Barone et al [ 16 ], and it is therefore not an independent value.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that both values were measured using different methods (namely, Knudsen effusion 29 and correlation gas chromatography 95 ). Despite the arguable superiority of the Knudsen effusion technique, 104 Diky et al argued 19 that the data point obtained by that method is a clear outlier from a strong correlation of sublimation enthalpies with molecular masses that is generally valid for caged hydrocarbons. 19 Comparison of the computed and experimental sublimation pressure data can be found in Figure 4, and in more detail in Table 4 and Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that both values were measured using different methods (namely Knudsen effusion 28 and correlation gas chromatography 27 ). Despite the arguable superiority of the Knudsen effusion technique, 83 Diky et al argued 19 that the data point obtained by that method is a clear outlier from a strong correlation of sublimation enthalpies with molecular masses that is generally valid for caged hydrocarbons. 19 Comparison of the computed and experimental sublimation pressure data can be found in Figure 4 and in more detail in Table 5.…”
Section: 25mentioning
confidence: 99%